2015
DOI: 10.1371/journal.pone.0117417
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Patient-Derived Orthotopic Xenograft (PDOX) Model of HER-2-Positive Cervical Cancer Expressing the Clinical Metastatic Pattern

Abstract: Squamous cell carcinoma of the cervix, highly prevalent in the developing world, is often metastatic and treatment resistant with no standard treatment protocol. Our laboratory pioneered the patient-derived orthotopic xenograft (PDOX) nude mouse model with the technique of surgical orthotopic implantation (SOI). Unlike subcutaneous transplant patient-derived xenograft (PDX) models, PDOX models metastasize. Most importantly, the metastasis pattern correlates to the patient. In the present report, we describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 26 publications
3
101
0
Order By: Relevance
“…Metastasis in nude mice included peritoneal dissemination, liver metastasis, lung metastasis, as well as lymph node metastasis, reflecting the metastatic pattern in the donor patient. Primary tumours and metastases in the nude mice had histological structures similar to those in the original tumour and were stained by a HER2-specific antibody in the same pattern as was the patient's cancer 14 .…”
mentioning
confidence: 92%
“…Metastasis in nude mice included peritoneal dissemination, liver metastasis, lung metastasis, as well as lymph node metastasis, reflecting the metastatic pattern in the donor patient. Primary tumours and metastases in the nude mice had histological structures similar to those in the original tumour and were stained by a HER2-specific antibody in the same pattern as was the patient's cancer 14 .…”
mentioning
confidence: 92%
“…Toward the goal of precision oncology, our laboratory pioneered the patient-derived orthotopic xenograft (PDOX) nude mouse model with the technique of surgical orthotopic implantation (SOI), including pancreatic, [1][2][3][4] breast, 5 ovarian, 6 lung, 7 cervical, 8 colon, [9][10][11] and stomach cancer, 12 sarcoma, [13][14][15][16][17] and melanoma. [18][19][20] In a previous study, we evaluated the efficacy of trabectedin (TRAB) and temozolomide (TEM) compared with cisplatinum (CDDP) on a lung-metastatic osteosarcoma PDOX mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Among these bacteria, S. enterica serovar Typhimurium strains have proven to be promising anticancer agents, which has led scientists to modify these bacteria to obtain strains with fewer side effects and improved therapeutic action [4,7,10-11,20,32-33]. Several studies have demonstrated that leu-arg auxotrophic S. enterica strain (A1-R) can effectively inhibit and in some cases even eradicate different types of primary and metastatic tumors when used as monotherapy in mouse models of prostate cancer [33-35], breast cancer [36][37][38], lung cancer [39,40], ovarian cancer [41,42], cervical cancer [43], pancreatic cancer [44][45][46][47][48], sarcoma [49][50][51] and glioma [52,53]. Recently, researchers have demonstrated that the S. enterica Typhimurium strain (STM) deficient for a zinc transporter operon can invade and proliferate in tumor cells, exerting therapeutic effect in the mammary adenocarcinoma mouse model by promoting an antitumor immune response [54].…”
Section: Discussionmentioning
confidence: 99%